2022
DOI: 10.1177/10556656221104942
|View full text |Cite
|
Sign up to set email alerts
|

American Indian and Alaska Native Accessibility to Comprehensive Cleft Lip and Palate Treatment

Abstract: American Indians and Alaska Natives (AI/AN) have the highest incidence of cleft lip and palate (orofacial clefts [OFCs]) when compared to other ethnic groups. We aim to determine the AI/AN populations’ proximity and accessibility to American Cleft Palate-Craniofacial Association accredited centers (ACPA centers) for treatment of OFCs. Our hypothesis is an unacceptable proportion of the AI/AN population lacks reasonable accessibility to ACPA centers and comprehensive craniofacial care. A cross-sectional study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…Typically, the American Indian and Alaska Native population has the highest rates of any facial cleft in the United States. 1,4,48 This population is captured in other races, as reported by the MSDH, and had an overall incidence of congenital anomalies that was three times higher than the average population rate, which corroborates our own findings. Interventions to address these discrepancies could begin with more accurate tracking of race and ethnicity by the MSDH.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Typically, the American Indian and Alaska Native population has the highest rates of any facial cleft in the United States. 1,4,48 This population is captured in other races, as reported by the MSDH, and had an overall incidence of congenital anomalies that was three times higher than the average population rate, which corroborates our own findings. Interventions to address these discrepancies could begin with more accurate tracking of race and ethnicity by the MSDH.…”
Section: Discussionsupporting
confidence: 88%
“…The reservation for the Mississippi Band of Choctaw Indians is located in the central region, and across the state, American Indians make up 0.6% of the population. Typically, the American Indian and Alaska Native population has the highest rates of any facial cleft in the United States 1,4,48 . This population is captured in other races, as reported by the MSDH, and had an overall incidence of congenital anomalies that was three times higher than the average population rate, which corroborates our own findings.…”
Section: Discussionsupporting
confidence: 86%
“…11 Furthermore, a recent geospatial study demonstrated that 47.1% of American Cleft Palate Craniofacial Association (ACPA) accredited centers situated in areas highly populated by American-Indian or Native American people were not staffed by craniofacial surgeons, compared to just 21.1% of ACPA centers nationwide. 12…”
Section: Resultsmentioning
confidence: 99%
“…One study demonstrated disparities in access to care specifically for Native-American or American-Indian patients. 12 However, it is important to note that this racial group was rarely included independently and was often combined with other racial groups due to a small sample size. As a result, it is possible that disparities for this racial group may be more prominent than reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation